Cotton Biotechnological Advances - Zehr, Usha B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The growing global population poses the challenge to the scientific community of doubling or tripling the food, feed and fiber production by the year 2050. Biotechnology can make a significant contribution to this effort. This volume reviews the use of biotechnology in cotton, which is the leading plant fiber crop worldwide and grown commercially in more than 50 countries. Renowned experts highlight the success of Bt cotton, the introduction of second and third generation traits and the impact at all levels of farming. Furthermore, the molecular advances being made in cotton biotechnology and the potential traits that will come to market in the next decade are described in detail.
Cotton: An Introduction -- Cotton in India -- Cotton Genomics -- Cotton Transformation -- New Tools and Traits for Cotton Improvement -- Insect Tolerant Cotton in India -- Insect Resistance Management for Transgenic Bt Cotton -- Opportunities for Engineering Abiotic Stress Tolerance in Cotton Plants -- Recent Advances in Molecular Biology Research on Cotton Fiber Development -- Global Adoption of Biotech Cotton, 1996 to 2007 -- Regulatory Systems and Requirements for Genetically Engineered Cotton from Lab to Land -- Socioeconomic Impacts of Bt (Bacillus thuringiensis) Cotton.
Keywords: Life sciences; Plant breeding; Life Sciences; Plant Breeding/Biotechnology.